Streamflow reconstructions from tree rings and variability in drought and surface water supply for the Milk and St. Mary River basins. (15th July 2022) - Martin, Justin T.; Pederson, Gregory T.
Abstract: The Milk and St. Mary Rivers are international waterways straddling the United States and Canada and traversing four Tribal Nations before draining into the Missouri and South Saskatchewan Rivers respectively. Management of water resources in the region is challenged by the complexity of stakeholder interests, the limitations of existing management infrastructure, and by a limited characterization of the long-term streamflow and hydroclimatic variability across the area. We used existing records of natural streamflow to investigate the relationships between seasonal climate variability and differences in the timing and volume of flow from the headwaters to the prairie tributaries. Then, using a network of tree-ring chronologies to reconstruct records of past streamflow, we assessed whether drought risk relates to these sub-basin specific differences and if drought events experienced during the observational period are representative of those that have occurred over the long-term. Observed climate-flow relationships suggest that outside of the mountain headwaters, where precipitation dominates the hydrograph, streamflow variability on lower reaches of the Milk River is particularly sensitive to winter temperatures. This sensitivity was reflected by severe drought conditions over the prairies during the 2000s, implying potentially large future flow reductions with warming. The streamflow reconstructions show sub-basin specific drought risks that also imply greater temperature driven drought severities across the prairie tributaries. Within the mountain and foothill sub-basins numerous past drought episodes exceed the magnitude and duration of observational period events, which implies the potential for future water supply management challenges stemming from severe, long-duration droughts coupled with the negative hydrologic effects of warmer temperatures. Highlights: Streamflow in the lower Milk Basin is strongly correlated with winter temperature. Early 2000s drought in the lower Milk Basin exceeded Dustbowl drought deficits. Reconstructed droughts exceeded instrumental events on the upper Milk and St. Mary.